Fat or lean: adjustment of endogenous energy stores to predictable and unpredictable changes in allostatic load. (8th October 2012) - Schultner, Jannik; Kitaysky, Alexander S.; Welcker, Jorg; Hatch, Scott; Boonstra, Rudy
Summary The ability to store energy endogenously is an important ecological mechanism that allows animals to buffer predictable and unpredictable variation in allostatic load. The secretion of glucocorticoids, which reflects changes in allostatic load, is suggested to play a major role in the adjustment of endogenous stores to these varying conditions. Although crucially important, the relationship between allostatic load and energy stores remains largely unexplored. Two contrasting hypotheses describe how stores may be adjusted: animals may use low allostatic loads to increase stores to a maximum possible ('fat and fit'), or they can attain a lean physique due to fitness advantages of a low body mass ('lean and fit'). We compiled observational and experimental data available for a long‐lived seabird to examine the relationship between glucocorticoids and stored energy at two life history stages (incubation and chick‐rearing). Data were collected across multiple years and colonies in the North Pacific, thereby reflecting the wide range of environmental conditions birds' encounter in the marine environment. During experimental manipulations, allostatic load was minimized by supplementing food to free‐living birds. We found that the relationship between allostatic load and energy stores was clearly curvilinear at both life history stages. Observational data suggested that energy stores remained relatively stable under low allostatic load and decreased under high loads. Experimental data showed that birds did not maximize energy stores under favourable conditions but maintained energy stores below a physiologically attainable level. Energy stores remained consistently lower during chick‐rearing compared to incubation across the wide range of variations in allostatic load suggesting that stage‐specific trade‐offs limit the accumulation of energy during favourable environmental conditions. Secretion of glucocorticoids did not appear to mediate this shift in energy stores between the life history stages. Overall, results of this study support the 'lean and fit' hypothesis. We conclude that increased energy stores may not necessarily reflect better environmental conditions experienced by individuals or predict their higher fitness. A major advantage of adopting a lean physique when environmental conditions allow may be the avoidance of additional energetic costs for moving a heavy body. In breeding seabirds, this advantage may be more important during chick‐rearing. In the focal species, the secretion of glucocorticoids might be involved in regulation of energy stores within a life history stage but does not appear to mediate an adaptive shift in energy stores between the incubating and chick‐rearing stages of reproduction.